The geogrid-reinforced gravel base pavement model - S.A. Matveev (Инженерно-строительный журнал, 2020)
The design model of reinforced crushed stone layer calculating as a multilayer plate on an elastic base using the technical theory of bending and the Bubnov-Galerkin method is proposed, which makes it possible to theoretically calculate and justify the effectiveness of using various types of geosynthetic materials for reinforcing pavement bases made of granular materials. The model is based on the hypothesis that the reinforced granular layer is deformed like a plate on an elastic base because of the mechanical connection with the geogrid. The calculating model is a multilayer plate consisting of an arbitrary number of solid homogeneous rigidly interconnected layers. The possibility of using this model for calculation of reinforced granular pavement base is confirmed experimentally. The results of the stamp tests showed satisfactory agreement with the results of theoretical studies. The discrepancy did not exceed 15 %.